Guidelines for online success : The Do's and Don'ts of the Internet from the best interactive agencies around the world /. - Ford, Rob, ....-; Wiedemann, Julius, ....- (Los Angeles : Taschen, 2011)
Have you ever wondered why your websites didn't quite match up to the success of your competitors or peers? Have you ever looked at other sites and thought: "Why didn't I think of that?" Have you ever spent too much time trying to find basic information that was buried deep in a needlessly complex website? You are certainly not alone and this book aims to change that by bringing together some of the world's most highly acclaimed designers and developers, spanning every continent, all of whom share their knowledge and experience. With chapters arranged by subject (interface and design, marketing and communication, technology and programming, technical advice, content/content management, and commerce), a clear do/don't structure, and plenty of real world examples of successful and award-winning websites, this book has all the advice and examples you will need to give your personal or business website an edge on its competitors and also win industry acclaim as well as respect from your peers. Your visitors will thank you.
Keywords: Social Media; Internet; Communication; Marketing